(untitled) (Scientific journal of the Fergana State University, 2023)
Based on the sources of the Timurid period, the article analyzes the reasoning about the conquest of Khorasan by Amir Timur in the book by the French historian of the XVII century Barthelemy d’Erbelo de Molenville “Oriental Library”.